Optimizing Clinical Processes to Accelerlate and Facilitate Patient Treatment in Outpatient Medical Clinics: A Comprehensive Review - Al Shariah, Ali Hussein Mohammad; Alyami, Rayid Hamad Hussein; Alyami, Ali Mohammad Ali; Al Qurai, Hassan Hamad Misfer; Alqahtani, Mohammad Hamad; Alazmi, Fehaid Eid; Alshammari, Mohammed Bedaiwi Fraih; Alsharyah, Turki Hussain Mohammed; Alaldbey, Hussain Hadi Ali; AlYami, Salem Samran Jahel (Journal of Posthumanism, 2024)
This comprehensive review examines the development of clinical processes that accelerate and facilitate patient treatment in outpatient medical clinics. Outpatient environments often face fragmented workflows, delayed treatment initiation, suboptimal handoff coordination, and documentation lag. Process redesign approaches including Lean healthcare, continuous quality improvement (CQI), and digital-enabled clinic workflows have shown measurable improvements in reducing time to treatment, optimizing clinic throughput, and supporting patient-centered care pathways. Technologies such as optimized Ambulatory EHR Systems, automated triage, and e-prescription integration serve as critical enablers to reduce bottlenecks, enhance interdisciplinary coordination between clinical units, standardize treatment triggers, and minimize process-related delays. The review recommends synthesizing global evidence regarding outpatient process maturity, clinical handoff efficiency, patient routing accuracy, and treatment activation timelines to inform scalable, safe, and operationally optimized process models for outpatient clinics.